PRODUCT ROTATIONAL ALIGNMENT FOR THE REACTION O(3P) + CS(X1-SIGMA+)-] CO(X1-SIGMA+) + S(3P) - Green, F; Hancock, G; Orrewing, A (1991)
Rotational alignment of the CO(X 1Σ+, v′ = 14) product of the O(3P) + CS(X 1Σ+) reaction has been measured relative to the velocity vector k of the reagents. O(3P) atoms were produced with k aligned in the laboratory frame by pulsed laser photolysis of NO2, and the CO product was detected by polarised laser-induced fluorescence. Transformation of the measured laboratory-frame rotational alignments to the required values of the alignment parameter 〈P2(J′ · k)〉 were carried out using previously determined values of the translational anisotropy for the photodissociation of NO2, making allowances for both the thermal distribution of CS radicals and the spread of recoil energies of the O-atom fragment. Values of 〈P2(J′ · k)〉 were measured for J′ between 12 and 35, and found to be close to zero to within the range 0 ± 0.25, with the mean value being slightly positive. Measurements of the Doppler profiles of the transitions are in qualitative agreement with those predicted for an isotropic distribution of product velocities about the k direction. These preliminary results illustrate the scope of laser based methods of extracting quantum-state-resolved data on scattering dynamics under experimental conditions which do not involve the use of molecular beam methods.